Design of a 3D Printed UWB Antenna for a Low-Cost Wireless Heart and Respiration Rate Monitoring - N. ‘A., Alias; S. M., Shaharum; M. S. A., Karim (IOP Publishing, 2020)
This paper introduces an ultra-wideband (UWB) horn antenna for a low-cost wireless heart and respiration rate monitoring that is manufactured by a 3D printing technology. The proposed design operates within 3.1-10.6 GHz. The horn antenna is designed within the 15-dB gain which is sufficient to be used in medical system. The horn was designed to calculate the gain in MATLAB using an approximation method and simulated using CST Microwave Studio. The proposed antenna is 4-6 GHz (G-Band) operating. A printed antenna which is supported by WR-187 rectangular waveguide is fabricated using low cost polylactic acid (PLA). The surface is then metalized using copper tape on the inside. The simulation result of reflection coefficient for different conductivity and thickness of coating metal is compared, the developed 3D printed antenna successfully operated within given frequency range of 3-11 GHz which covered the ultra-wideband frequency range.